Glycerol acetylation considering competing dimerization. Issue 8 (29th April 2019) - Soares, André V.‐H.; Kale, Sumeet S.; Armbruster, Udo; Passos, Fabio B.; Umbarkar, Shubhangi B.; Dongare, Mohan K.; Martin, Andreas
Abstract: Glycerol acetylation is a very interesting reaction for studies of consecutive kinetics. In this short communication, we present a pseudo‐homogeneous model for the synthesis of triacetyl glycerol from the reaction of glycerol and acetic acid over strongly acidic Amberlyst‐15 and Amberlyst‐70 catalysts, considering a dimerization of diacetyl glycerol (DAG) into diglycerol tetraacetate as a parallel reaction and compare the results with a model without side reactions. The best fits were obtained for apparent zeroth‐order dimerization and first‐order consecutive reactions in the presence of acetic acid in excess and with removal of water. An adaptation was made for DAG. The proposed model shows that the formation of DAG is faster than the consumption of glycerol, which could be an explanation for the occurrence of DAG dimerization instead of other parallel reactions in acetylation.